Criminal Tendencies in Adolescents and their Correlation to Depression - Qamar Yasmeen; Nighat Yasmeen; Summaira Yasmeen (Gandhara University, 2023)
OBJECTIVES The study aimed to investigate the correlation between criminal tendencies and depression among young adults and to find out the relationship between these variables. Gender differences in these variables were also studied. METHODOLOGY A cross-sectional study was conducted in the city of Faisalabad over the period of 6 Months from January 2022 to June 2022. Young adults aged 15-25 were included in the study. Sample 300 participants, including 150 males and 150 females, through a convenient sampling technique. A structured questionnaire consisting of sociodemographic, depression and criminal tendency questions was used to collect data. Correlation analysis was performed to measure the correlation between criminal tendency and depression among youth. An independent sample T-test was used to get gender differences. RESULTS The findings of the study also revealed some significant correlation between criminal tendencies and depression among young adults. However, gender differences exist between criminal tendencies and depression, as males got higher scores than females. CONCLUSION The results of the research show a strong correlation between juvenile depressive disorders and criminal tendencies. Finding the causes of adult depression is also necessary to prevent future crimes related to depression.